2018
DOI: 10.3389/fimmu.2018.00223
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages in the Human Cochlea: Saviors or Predators—A Study Using Super-Resolution Immunohistochemistry

Abstract: The human inner ear, which is segregated by a blood/labyrinth barrier, contains resident macrophages [CD163, ionized calcium-binding adaptor molecule 1 (IBA1)-, and CD68-positive cells] within the connective tissue, neurons, and supporting cells. In the lateral wall of the cochlea, these cells frequently lie close to blood vessels as perivascular macrophages. Macrophages are also shown to be recruited from blood-borne monocytes to damaged and dying hair cells induced by noise, ototoxic drugs, aging, and diphth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
109
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(120 citation statements)
references
References 70 publications
8
109
0
Order By: Relevance
“…Significantly increased necroptosis protein, RIPK3, was significantly increased in the organ of Corti and stria vascularis. Recent studies have identified both resident macrophages (CD163-, IBA1-, and CD68-positive cells) and migrated macrophages in the human cochlea [55,56]. It is well-known that IL-1 and IL-6 are important modulators of the innate and adaptive immune responses [57].…”
Section: Discussionmentioning
confidence: 99%
“…Significantly increased necroptosis protein, RIPK3, was significantly increased in the organ of Corti and stria vascularis. Recent studies have identified both resident macrophages (CD163-, IBA1-, and CD68-positive cells) and migrated macrophages in the human cochlea [55,56]. It is well-known that IL-1 and IL-6 are important modulators of the innate and adaptive immune responses [57].…”
Section: Discussionmentioning
confidence: 99%
“…43 Furthermore, active IBA-immunopositive cells were also found to be closely associated with the OHCs in the human inner ear. 44 Whether macrophages are derived from activated resident cells or represent externally recruited cells remains unknown.…”
Section: Human Otic Progenitor Transplantation Triggered An Immune Rementioning
confidence: 99%
“…A necroptotic response in the inner ear thus would only make sense if the inner ear was not "immune privileged," as historically assumed, but was capable of mounting a significant immunological response. In fact, more recent studies suggest that the resolution of ototoxic insults is aided by immune cells infiltrating into the inner ear (Kaur et al, 2015a(Kaur et al, ,b, 2018Francis and Cunning-ham, 2017;Mizushima et al, 2017;Wood and Zuo, 2017;Barald et al, 2018;Liu et al, 2018). Such immune activity, beneficial under normal circumstances, might become counterproductive when ototoxins overwhelm the system, creating a massive, detrimental immune response.…”
Section: Discussionmentioning
confidence: 99%